The role of iron in the skin and cutaneous wound healing - Wright, Josephine A.; Richards, Toby; Srai, Surjit K. S. (Frontiers in Pharmacology, 2014)
In this review article we discuss current knowledge about iron in the skin and the cutaneous wound healing process. Iron plays a key role in both oxidative stress and photo-induced skin damage. The main causes of oxidative stress in the skin include reactive oxygen species (ROS) generated in the skin by ultraviolet (UVA) 320-400 nm portion of the ultraviolet spectrum and biologically available iron. We also discuss the relationships between iron deficiency, anaemia and cutaneous wound healing. Studies looking at this fall into two distinct groups. Early studies investigated the effect of anaemia on wound healing using a variety of experimental methodology to establish anaemia or iron deficiency and focused on wound-strength rather than effect on macroscopic healing or re-epithelialisation. More recent animal studies have investigated novel treatments aimed at correcting the effects of systemic iron deficiency and localised iron overload. Iron overload is associated with local cutaneous iron deposition, which has numerous deleterious effects in chronic venous disease and hereditary haemochromatosis. Iron plays a key role in chronic ulceration and conditions such as Rheumatoid Arthritis (RA) and Lupus Erythematosus are associated with both anaemia of chronic disease and dysregulation of local cutaneous iron haemostasis. Iron is a potential therapeutic target in the skin by application of topical iron chelators and novel pharmacological agents, and in delayed cutaneous wound healing by treatment of iron deficiency or underlying systemic inflammation.